An analysis of the perceived difficulties arising during the process of integrating management systems - Jesus Abad; Henrry Ricardo Cabrera; Alberto Medina-León (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: This study empirically scrutinises the difficulties that result from the integration of management systems and analyses the role of strategic actions and organisational factors on the difficulties-integration relationship. Design/Methodology/Approach: For the empirical application we use a unique dataset of Spanish certified firms (ISO 9001, ISO 14001 and OHSAS 18001) with integrated management system. We employ an analysis based on nonparametric tests to detect differences in the distribution of perceived difficulties across groups of firms grouped according to strategic choices and business size. Findings: Results show that the most relevant difficulty faced by managers is the employees' resistance to chance. Also, results suggest that the effective integration of management systems is conditioned by the sequence of integration of the systems, the integration level achieved and the structure governing the new integrated system. We also report a negative relationship between perceived difficulties and firm size. Practical implications: For business strategists, our results underline the relevance of designing governance structures that match the requirements of the integrated system and interlock organisational and technical aspects at the design stage of the new integrated system. Additionally, the findings suggest that managers should also develop communication actions that increase the participation and involvement of workers at all stages of the integration process. Originality/value: Most research emphasises the benefits of integrated management systems. By analysing the difficulties that arise during the integration process, this study contributes to fill a gap in the literature on the problems associated with processes of organisational change, in our case the integration of management systems.
Keywords: 650; integrated management systems; ISO 9001; ISO 14001; OHSAS 18001; perceived difficulties